Antibacterial Polyketides from the Marine Alga-Derived Endophitic Streptomyces sundarbansensis: A Study on Hydroxypyrone Tautomerism - Ines Mancini; Andrea Defant; Ibtissem Djinni; Mouloud Kecha (Marine Drugs, 2013)
Polyketide 13 [=2-hydroxy-5-((6-hydroxy-4-oxo-4H-pyran-2-yl)methyl)-2- propylchroman-4-one] and three related known compounds 7, 9 and 11 were obtained and structurally characterized from Streptomyces sundarbansensis strain, an endophytic actinomycete isolated from the Algerian marine brown algae Fucus sp. Compound 13 was obtained as the major metabolite from optimized culture conditions, by using Agar state fermentation. Due to tautomeric equilibrium, 13 in CD3OD solution was able to incorporate five deuterium atoms, as deduced by NMR and ESI-MS/MS analysis. The 2-hydroxy-γ-pyrone form was established for these metabolites based on the comparison of their experimental IR spectra with the DFT calculated ones, for both the corresponding 4-hydroxy-α-pyrone and 2-hydroxy-γ-pyrone forms. During antibacterial evaluation, compound 13 stood out as the most active of the series, showing a selective activity against the gram positive pathogenic methicillin-resistant S. aureus (MRSA, MIC = 6 μΜ), with a bacteriostatic effect.